Hedging Downside Risk: Futures Versus Options - TSE, Yiu Kuen (Institutional Knowledge at Singapore Management University, 2001)
In this paper, we compare the hedging effectiveness of currency futures vs. currency options on the basis of the lower partial moments (LPMs). The LPM measures an individual hedger's downside risk, as opposed to the two-sided risk measure. Two estimation methods are applied to estimate the optimal hedge ratio: the empirical distribution function method and the kernel density estimation method. We consider both methods for three currencies: the British pound, the Deutsche mark, and the Japanese yen. Currency futures are found to be a better hedging instrument than currency option.